Toksisitas Ekstrak Biji Mahoni Terhadap Ulat Plutella xylostella pada Daun Kubis - Ayu Putri Dwi Ariyanti; Subagiya Subagiya; Ato Sulistyo (Universitas Sebelas Maret, 2020)
Plutella xylostella is one of cabbage’s main pests. Botanical insecticides as alternative of chemical insecticides need to be expand, one of them is mahogany seed extract. Mahogany seed exctract contains saponin and flavonoid as reported mortal to P. xylostella. This study aimed to know the effective concentration of mahogany seed extract to manage P. xylostella different larva instar and to know LC50 value of mahogany seed extract to P. xylostella. This method used was completely randomized experimental design (CRD). Two factors used were mahogany seed exctract concentrations (0 gL-1, 5 gL-1, 10 gL-1, 20 gL-1, and 40 gL-1) and larva instar (first and third instar). Each treatment repeated four times. The results showed that percentage of larva mortality first instar higher than third instar. Concentration 20 gL-1 of mahogany seed exctract effective to kill first instar larva, and concentration 40 gL-1 effective for third instar. Percentage of pupa mortality highest in concentration 10 gL-1 for first instar and concentration 40 gL-1 for third instar larva. Antifeedant increased as concentration given, while the eating ability that higher in third instar was decreased. LC50 for first instar larva was 2,6 gL-1 and third instar was 13,7 gL-1, meaned that mahogany seed extract more toxic to first instar than third instar larva.